A method for preparing a high specific surface area nitrogen-doped carbon electrocatalyst
By retaining Zn in ZIF-8 and performing high-temperature gas-phase reaction with SbCl3 and cobalt hexaamide chloride, a nitrogen-doped carbon electrocatalyst with a high specific surface area was prepared, which solved the problems of slow kinetics of existing oxygen reduction electrocatalysts and high cost of precious metal catalysts, and achieved excellent oxygen reduction performance and stability.
Patent Information
- Application Number
- CN202211091943.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-07
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-09-07
AI Technical Summary
The existing oxygen reduction electrocatalysts have slow kinetics in cathode oxygen reduction reactions, and precious metal catalysts such as Pt are scarce and costly, limiting their commercial applications.
By sealing ZIF-8 and calcining at different temperatures at high temperatures, Zn is retained, and then the surface adsorbs the low-melting salt SbCl3, and finally undergoing a high-temperature gas-phase reaction with cobalt hexaamino chloride, a nitrogen-doped carbon electrocatalyst with a high specific surface area was prepared.
This electrocatalyst has a very high specific surface area and rich micro/mesoporous, excellent electrocatalytic performance and good stability, and has potential application value in the field of oxygen reduction.
Smart Images

Figure 220906160238 
Figure 220906160241 
Figure 220906160244
Abstract
Description
Technical Field
[0001] The present invention relates to a class of highly efficient and inexpensive oxygen reduction electrocatalysts, and in particular to a preparation method and oxygen reduction performance of a high specific surface area nitrogen-doped carbon electrocatalyst, belonging to the field of oxygen reduction applications. Background Art
[0002] Rechargeable zinc-air batteries have attracted extensive attention from researchers due to their high energy density, high zinc reserves, low cost and high safety. The cathode oxygen reduction reaction (ORR) involves a multi-step proton-coupled electron transfer process with slow kinetics. Compared with non-precious metal materials, Pt-based catalysts have high activity. However, the scarcity and high cost of Pt resources limit their commercial application. In this regard, positive progress has been made in the research of non-precious metal catalysts, among which nitrogen-doped carbon (NCs) systems with large specific surface areas have become a research hotspot. At present, there are two main strategies to optimize the performance of this type of catalyst: one is to improve the intrinsic activity of nitrogen sites, and the other is to increase the number of effective active sites of the catalyst.
[0003] Nitrogen-doped carbon materials with high specific surface area and porosity have multiple advantages: high specific surface area can expose more electrocatalytic active sites, while high porosity can improve the transport of electrons / ions, achieve efficient electrolyte / reactant transport, and improve electrocatalytic efficiency. Metal organic frameworks (MOFs) have been widely used in renewable energy and environmental aspects due to their high porosity, organic-inorganic hybrid properties, and inherent metal and heteroatoms. Taking ZIF-8 as an example, through high-temperature calcination, the Zn in it will be released in the form of vapor, thus forming a large number of pores in the derived product. Summary of the invention
[0004] Based on the above technical problems, the present invention seals ZIF-8 and calcines it at different temperatures to retain the Zn therein, then adsorbs the low melting point salt SbCl3 on the surface, and finally reacts with hexaammine cobalt chloride at high temperature to obtain a nitrogen-doped carbon electrocatalyst. During the high-temperature gas phase reaction (> 800°C), since hexaammine cobalt chloride will be reduced in the gas phase, the pyrolysis of the precursor is accelerated. At the same time, it can promote the Zn retained in ZIF-8 and the adsorbed Sb to escape in the form of vapor, thereby creating a large number of pore structures in the nitrogen-doped carbon. The electrocatalyst has a very high specific surface area and abundant micro / mesopores, so it has excellent electrocatalytic performance and good stability, and has potential application value in the field of oxygen reduction. The object of the present invention is to provide a nitrogen-doped carbon electrocatalyst with a high specific surface area and excellent oxygen reduction performance. The specific steps of its preparation method are:
[0005] The preparation method of the nitrogen-doped carbon electrocatalyst is:
[0006] Step 1: Dissolve Zn(NO3)2·6H2O in methanol to obtain solution A; then dissolve 2-methylimidazole in methanol to obtain solution B; mix solutions A and B, stir evenly, and stand at a constant temperature overnight, then centrifuge and wash the obtained product with methanol, and vacuum dry to obtain a ZIF-8 precursor;
[0007] Step 2: The ZIF-8 precursor is sealed and pyrolyzed at high temperature under Ar atmosphere to obtain Zn / NC powder;
[0008] Step 3: Prepare an ethanol solution of SbCl3, add Zn / NC powder to soak and stir, then centrifuge and wash with ethanol, and vacuum dry to obtain Zn / NC@SbCl3;
[0009] Step 4: Place Zn / NC@SbCl3 in the center of the tube furnace, and then place hexaammine cobalt chloride upstream of the tube furnace, and perform high-temperature gas-phase reaction under Ar atmosphere to obtain the product nitrogen-doped carbon electrocatalyst.
[0010] In the step 1, the mass ratio of Zn(NO3)2·6H2O to 2-methylimidazole is 1:0.8-1.5.
[0011] In the step 2, the ZIF-8 precursor is subjected to sealed high-temperature pyrolysis at a temperature of 700-900°C.
[0012] In the step 3, the mass ratio of Zn / NC powder to SbCl3 is 1:0.5-2.
[0013] In the step 4, the mass ratio of Zn / NC@SbCl3 to hexaamminecobalt chloride is 3-5:1.
[0014] In the step 4, Zn / NC@SbCl3 and hexaamminecobalt chloride are not in contact, and the interval between them is more than 1 cm.
[0015] The high temperature gas phase reaction temperature in step 4 is 900-1000°C.
[0016] In step 2, the ZIF-8 precursor is sealed and pyrolyzed at high temperature to retain a large amount of Zn, and the introduction of hexaammine cobalt chloride can promote the release of these Zn in the form of gas phase during the subsequent high-temperature pyrolysis process, thereby creating a large number of micro / mesopores and increasing the specific surface area of the product to 2000 m² g -1 The pore volume increases to 1.7 m 3 g -1 about.
[0017] The nitrogen-doped carbon electrocatalyst and preparation method involved in the present invention have the following significant features:
[0018] (1) High specific surface area and porosity (2016 m² g -1 , 1.71 m 3 g -1 ).
[0019] (2) It has excellent electrocatalytic oxygen reduction activity and good stability, and has potential applications in the field of oxygen reduction. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 XRD pattern and SEM image of Zn / NC prepared in Example 1.
[0021] Figure 2 XRD and Raman spectra of the samples prepared in Examples 1, 2 and 3, where (a) is the XRD spectrum and (b) is the Raman spectrum.
[0022] Figure 3 (a) is the TEM image of the sample prepared in Example 1, and (b) is the TEM image of the sample prepared in Example 3.
[0023] Figure 4 N2 adsorption-desorption curve and particle size distribution diagram of the sample prepared in Example 2, where (a) is the N2 adsorption-desorption curve of the sample, and (b) is the pore size distribution diagram.
[0024] Figure 5 LSV diagrams of the samples prepared in Examples 1, 2 and 3.
[0025] Figure 6 Oxygen reduction electron transfer number (n) and H2O2 yield of the samples prepared in Examples 1, 2, and 3.
[0026] Figure 7 Stability diagram of the sample prepared in Example 2 and Pt / C.
[0027] Figure 8 LSV diagrams of comparison samples NC-4 and NC-5. DETAILED DESCRIPTION
[0028] Example 1
[0029] A method for preparing a high specific surface area nitrogen-doped carbon electrocatalyst, the method for preparing the nitrogen-doped carbon electrocatalyst is:
[0030] Step 1: Dissolve 7.88 g Zn(NO3)2·6H2O in 200 mL methanol to obtain solution A; then dissolve 7.14 g 2-methylimidazole in 200 mL methanol to obtain solution B. Mix solutions A and B, stir evenly, and keep at 60 °C for 24 h. Then, wash the obtained product with methanol by centrifugation for 3-4 times, and finally dry it in a vacuum drying oven for 12 h to obtain the ZIF-8 precursor.
[0031] Step 2: Spread ZIF-8 flatly in a corundum boat, seal it, and then pyrolyze it at 800 °C in a tube furnace under Ar atmosphere to obtain Zn / NC powder.
[0032] Step 3: Prepare 10 mM SbCl3 ethanol solution, add 100 mg Zn / NC powder, soak and stir for 2 h, then centrifuge and wash with ethanol, and put it in a vacuum drying oven to obtain Zn / NC@SbCl3.
[0033] Step 4: Place 100 mg of Zn / NC@SbCl3 in the center of the tube furnace, and then place 25 mg of hexaamminecobalt chloride ([Co(NH3)6]Cl3) 1 cm upstream of the tube furnace. Raise the temperature to 900°C at 5°C / min in an Ar atmosphere and keep the temperature constant for 2 h for a high-temperature gas phase reaction to obtain the product NC-2.
[0034] Figure 1 The XRD spectrum and scanning electron microscope photos of Zn / NC powder obtained under 800 ℃ sealing conditions are given. It can be seen that only the diffraction peaks of graphitized carbon (002) and (101) crystal planes appear in the Zn / NC sample, and the rhombic dodecahedron morphology of ZIF-8 is maintained. Due to sealing, the Zn content in the Zn / NC powder obtained under this condition is 21 wt.%. These Zns will escape in the form of vapor during the subsequent fourth step annealing treatment, thereby creating a large number of micro / mesopores.
[0035] Figure 2 (a) is the XRD spectrum of NC-2, the catalyst prepared in this example. It can be seen from the figure that this sample only has o and 44 o Two broad diffraction peaks appear on the left and right, corresponding to the (002) and (101) crystal planes of graphitized carbon. Figure 2 The Raman spectrum in b shows that NC-2 is also at 1343 cm-1, which is the same as NC-1. -1 and 1584 cm -1 The carbon D peak and G peak appear at the positions. By calculation, the peak intensities of D peak and G peak (I D / I G ) is also equal to 1. The sample obtained in this example was analyzed by transmission electron microscopy (such as Figure 3 As shown in a), it can be observed that the sample retains the original rhombic dodecahedron shape of ZIF-8, with a size of about 200 nm. Figure 4 a is the N2 adsorption-desorption curve of the sample. Through calculation, it is known that the specific surface area of NC-2 catalyst is as high as 2016 m² g -1 . Further, by Figure 4 From the pore size distribution diagram of b, we can see that the pore size distribution in the NC-2 sample is mainly micropores, followed by mesopores, and the total pore volume reaches 1.71 m 3 g -1 High specific surface area and porosity are crucial to improving the utilization efficiency of catalytic active sites, enhancing the mass transfer rate of reaction substrates and catalytic products at the electrode interface, and ultimately improving the ORR performance of the material. The sample was used to prepare a slurry, and its ORR performance was tested in an O2-saturated 0.1M KOH solution using a rotating disk electrode (RDE). Figure 5 NC-2 is its LSV curve. It can be seen from the figure that at 1600 rpm, its half-wave potential is 0.88 V vs. RHE and the limiting current density is 5.6 mA cm -2 , also showing excellent ORR activity. Figure 6 The ring-disk test results of the samples prepared in this example show that the number of electrons transferred by the NC-2 electrocatalyst in the oxygen reduction reaction is close to the theoretical value of 4, and the by-product yield is less than 13%, which is close to that of commercial Pt / C, indicating that the reaction pathway of the catalyst is 4e - Process-oriented. Figure 7 This is the ORR stability diagram of the sample prepared in this example. It can be seen from the figure that at 1600 rpm, after 7200 s, the current of NC-2 only decays by 0.9%, while the commercial Pt / C decays by 23.2%, indicating that the sample has excellent oxygen reduction stability.
[0036] Example 2
[0037] A method for preparing a high specific surface area nitrogen-doped carbon electrocatalyst, the method for preparing the nitrogen-doped carbon electrocatalyst is:
[0038] Step 1: Dissolve 7.88 g Zn(NO3)2·6H2O in 200 mL methanol to obtain solution A; then dissolve 7.14 g 2-methylimidazole in 200 mL methanol to obtain solution B. Mix solutions A and B, stir evenly, and keep at 60 °C for 24 h. Then, wash the obtained product with methanol by centrifugation for 3-4 times, and finally dry it in a vacuum drying oven for 12 h to obtain the ZIF-8 precursor.
[0039] Step 2: Spread ZIF-8 flatly in a corundum boat, seal it, and then pyrolyze it at 700 °C in a tube furnace under Ar atmosphere to obtain Zn / NC powder.
[0040] Step 3: Prepare 10 mM SbCl3 ethanol solution, add 100 mg Zn / NC powder, soak and stir for 2 h, then centrifuge and wash with ethanol, and put it in a vacuum drying oven to obtain Zn / NC@SbCl3.
[0041] Step 4: Place 100 mg Zn / NC@SbCl3 in the center of the tube furnace, and then place 25 mg hexaammine cobalt chloride ([Co(NH3)6]Cl3) 1 cm upstream of the tube furnace. o The temperature was raised to 900 °C at a rate of 100 °C / min and maintained at this temperature for 2 h for high-temperature gas phase reaction to obtain the product NC-1.
[0042] The Zn / NC powder obtained in this example has the same phase and morphology as those in Example 1, except that the Zn content in the Zn / NC powder is 31 wt.%. Figure 2 NC-1 in b is the Raman spectrum of the catalyst prepared in this example. As can be seen from the figure, at 1343 cm -1 and 1584 cm -1 The carbon D peak and G peak appear at the positions. By calculation, the peak intensities of D peak and G peak (I D / I G ) is equal to 1, indicating that the carbon in NC-1 is successfully graphitized and contains a certain amount of defects, which is very beneficial for the catalytic oxygen reduction process. The sample of this example was dispersed in a solvent and then dropped onto a rotating disk electrode to form a film, and its ORR performance was tested in an O2-saturated 0.1M KOH solution. Figure 5 NC-1 is its LSV curve. It can be seen from the figure that at 1600 rpm, the half-wave potential of NC-1 is 0.88 V vs. RHE and the limiting current density is 5.5 mA cm -2 , excellent electrocatalytic activity. Figure 6 The results of the ring-disk test of the sample prepared in this embodiment can be seen from the figure. In the oxygen reduction reaction of the NC-1 electrocatalyst, the number of transferred electrons is close to the theoretical value of 4, and the by-product yield is only 5%, indicating that the reaction path of NC-1 catalyzing oxygen reduction is 4e - Process-oriented.
[0043] Example 3
[0044] Step 1: Dissolve 7.88 g Zn(NO3)2·6H2O in 200 mL methanol to obtain solution A; then dissolve 7.14 g 2-methylimidazole in 200 mL methanol to obtain solution B. Mix solutions A and B, stir evenly, and keep at 60 °C for 24 h. Then, wash the obtained product with methanol by centrifugation for 3-4 times, and finally dry it in a vacuum drying oven for 12 h to obtain the ZIF-8 precursor.
[0045] Step 2: Spread ZIF-8 flatly in a corundum boat, seal it, and then pyrolyze it at 900 °C in a tube furnace under Ar atmosphere to obtain Zn / NC powder.
[0046] Step 3: Prepare 10 mM SbCl3 ethanol solution, add 100 mg Zn / NC powder, soak and stir for 2 h, then centrifuge and wash with ethanol, and put it in a vacuum drying oven to obtain Zn / NC@SbCl3.
[0047] Step 4: Place 100 mg Zn / NC@SbCl3 in the center of the tube furnace, and then place 25 mg hexaammine cobalt chloride ([Co(NH3)6]Cl3) 1 cm upstream of the tube furnace. o The temperature was raised to 900 °C at a rate of 100 °C / min and maintained at this temperature for 2 h for high-temperature gas phase reaction to obtain the product NC-3.
[0048] The Zn / NC powder obtained in this example has the same phase and morphology as those in Example 2, except that the Zn content in the Zn / NC powder is 12 wt.%. Figure 2 NC-3 in a is the XRD spectrum of the catalyst prepared in this example. It is the same as that in Examples 1 and 2. o and 44 o Diffraction peaks corresponding to the (002) and (101) crystal planes of graphitized carbon appear on the left and right. Figure 2 The Raman spectrum in b shows that NC-3 is also at 1343 cm, which is the same as NC-1 and NC-2. -1 and 1584 cm -1 The carbon D peak and G peak appear at the positions, but the difference is that the peak intensities of D peak and G peak (I D / I G ) was slightly improved to 1.03. The obtained samples were further analyzed by transmission electron microscopy (such as Figure 3 As shown in (b), it can be observed that the NC-3 sample also retains the rhombic dodecahedron shape of ZIF-8. The slurry was prepared with this sample and its ORR performance was tested in an O2-saturated 0.1M KOH solution using a rotating disk electrode (RDE). Figure 5NC-3 is its LSV curve. It can be seen from the figure that at 1600 rpm, its half-wave potential is 0.85 V vs. RHE and the limiting current density is 5.2 mA cm -2 , slightly lower than NC-1 and NC-2. Figure 6 This is the ring-disk test result of the sample prepared in this example. It can be seen from the figure that in the oxygen reduction reaction, the number of transferred electrons of the NC-3 electrocatalyst is 3.5, close to the theoretical value of 4, and its by-product yield is less than 25%.
[0049] Compared with Example 3, the experimental steps and the dosage of other chemicals remain unchanged, and only the sealing is not performed during the high-temperature pyrolysis of the ZIF-8 precursor. The ORR LSV curve of the obtained sample NC-4 is as follows: Figure 8 As shown in the figure, at 1600 rpm, its half-wave potential is only 0.84 V vs. RHE, and the limiting current density drops to 5 mA cm -2 , indicating its poor ORR performance.
[0050] If the experimental steps and the dosage of other chemicals are kept unchanged, the high-temperature pyrolysis temperature of the ZIF-8 precursor is increased to 1000°C, and the ORR LSV curve of the obtained sample NC-5 is as follows: Figure 8 As shown in the figure, at 1600 rpm, its half-wave potential drops to 0.83 V vs. RHE and the limiting current density drops to 5 mA cm -2 , its ORR performance is obviously attenuated.
Claims
1. A method for preparing a high specific surface area nitrogen-doped carbon electrocatalyst, characterized in that: The preparation method of the nitrogen-doped carbon electrocatalyst is: Step 1: Dissolve Zn(NO3)2·6H2O in methanol to obtain solution A; then dissolve 2-methylimidazole in methanol to obtain solution B; mix solutions A and B, stir evenly, and stand at a constant temperature overnight, then centrifuge and wash the obtained product with methanol, and vacuum dry to obtain a ZIF-8 precursor; Step 2: The ZIF-8 precursor is sealed in an Ar atmosphere and subjected to high-temperature pyrolysis to obtain Zn / NC powder. The high-temperature pyrolysis temperature of the ZIF-8 precursor is 700-900°C; Step 3: Prepare an ethanol solution of SbCl3, add Zn / NC powder to soak and stir, then centrifuge and wash with ethanol, and vacuum dry to obtain Zn / NC@SbCl3; Step 4: Place Zn / NC@SbCl3 in the center of the tube furnace, and then place hexaammine cobalt chloride upstream of the tube furnace, and carry out high-temperature gas-phase reaction under Ar atmosphere to obtain the product nitrogen-doped carbon electrocatalyst. The high-temperature gas-phase reaction temperature is 900-1000°C.
2. The method for preparing a high specific surface area nitrogen-doped carbon electrocatalyst according to claim 1, characterized in that: In step 1, the mass ratio of Zn(NO3)2·6H2O and 2-methylimidazole is 1:0.8-1.
5.
3. The method for preparing a high specific surface area nitrogen-doped carbon electrocatalyst according to claim 1, characterized in that: In step 3, the mass ratio of Zn / NC powder to SbCl3 is 1:0.5-2.
4. The method for preparing a high specific surface area nitrogen-doped carbon electrocatalyst according to claim 1, characterized in that: In step 4, the mass ratio of Zn / NC@SbCl3 to hexaamminecobalt chloride is 3-5:
1.
5. The method for preparing a high specific surface area nitrogen-doped carbon electrocatalyst according to claim 4, characterized in that: In step 4, Zn / NC@SbCl3 and hexaamminecobalt chloride are not in contact, and the interval is more than 1 cm.
Citation Information
Patent Citations
Preparation method and application of Sb / NC electrocatalyst
CN113903928A